Agreement between optometrists and ophthalmologists on clinical management decisions for patients with glaucoma. Issue 5 (18th April 2006) - Banes, M J; Culham, L E; Bunce, C; Xing, W; Viswanathan, A; Garway-Heath, D
Abstract : Background/aims: Although optometrists have become an accepted part of the team in many hospital glaucoma clinics, their decision making ability has not been assessed formally. This study aims to document the accuracy and safety of clinical work undertaken by optometrists in the hospital setting by investigating their management decisions on follow up of patients with glaucoma. Methods: Four optometrists and three medical clinicians examined 50 patients each. Clinical findings were recorded as usual in the hospital records but management decisions were documented separately on a specially designed data collection form. Subsequently, the patient records and clinical findings were reviewed retrospectively and independently by two consultant ophthalmologists, who were masked to the management decisions of the optometrists and medical clinicians. The consultants' management decisions were then compared with those made by the optometrists and medical clinicians. Percentage agreements were computed together with kappa (κ), or weighted kappa, statistics where appropriate. Results: Agreement between consultants and optometrists was 55% (κ = 0.33) for evaluation of visual field status, 79% (κ = 0.67) for medical management, 72–98% for other aspects of patient management, and 78% (weighted κ = 0.35) for scheduling of next clinic appointment. Very similar levels of agreement were found between consultants and medical clinicians. Conclusion: Agreement between optometrists and consultants, in glaucoma clinical decision making, was at least as good as that between medical clinicians and consultants. Within an appropriate environment, optometrists can safely work as part of the hospital glaucoma team in outpatient clinics.